Online graduate job vacancies system / Noreen Natasya Aziz Al-Rahim - Noreen Natasya , Aziz Al-Rahim (2003)
Internet is fast becoming an important part of our everyday lives. More and more,people are integrating internet application into their daily lives whether it's to read and write email. shop transfer files listen to music, send picture , pay bill look for a house or find a job. As the web culture of the new millennium pervades society, people are increasingly beginning to recognize the advantages and convenience of the internet. Online Graduate Job Vacancies System is designed and developed based on the principal. It is an online employment and recruitment portal that provides recruiting services for both employers and potential employees. The system aims to provide fast, efficient and reliable alternative in job seeking. In traditional way, the HR department waits for all applications to come in by the closing date, sorts them, makes copies of the resumes to pass on those who will be involved in the interview, get feedback on whom the shortlist before finally getting back to the applicants. This whole process is very time consuming and it is not piratical in today's pace of life. System eliminates the inefficiencies by offering job marching service that will match candidates to jab vacancies based on requirements and preference of both parties. The development process of Online Graduate Job Vacancies System involves several stages which include literature review, system analysis and requirement and system design. Each of the stage will be described further in the report. The report will also covers the process model, the research plan and methodologies, the analysis on existing system and the design of the new system. System will be using multi-tier client/server software architecture and ASP as the web programming tool. System will be Using Microsoft SQL Server 7.0 for its' database implementation.